2016
DOI: 10.1371/journal.pntd.0005093
|View full text |Cite
|
Sign up to set email alerts
|

Containing Ebola at the Source with Ring Vaccination

Abstract: Interim results from the Guinea Ebola ring vaccination trial suggest high efficacy of the rVSV-ZEBOV vaccine. These findings open the door to the use of ring vaccination strategies in which the contacts and contacts of contacts of each index case are promptly vaccinated to contain future Ebola virus disease outbreaks. To provide a numerical estimate of the effectiveness of ring vaccination strategies we introduce a spatially explicit agent-based model to simulate Ebola outbreaks in the Pujehun district, Sierra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 21 publications
2
68
0
Order By: Relevance
“…The ring vaccination strategy identifies and vaccinates contacts of infectious individuals, as well as contacts of contacts. Recent studies have used a network-based transmission agent-based model [14] and spatially explicit agentbased models [1,46] to examine the impact of ring vaccination of EVD outbreaks using data from the 2014 West Africa Outbreak. The explicit inclusion of space within the model follows the modeling approach of ring vaccination models for foot and mouth disease [47,37].…”
mentioning
confidence: 99%
“…The ring vaccination strategy identifies and vaccinates contacts of infectious individuals, as well as contacts of contacts. Recent studies have used a network-based transmission agent-based model [14] and spatially explicit agentbased models [1,46] to examine the impact of ring vaccination of EVD outbreaks using data from the 2014 West Africa Outbreak. The explicit inclusion of space within the model follows the modeling approach of ring vaccination models for foot and mouth disease [47,37].…”
mentioning
confidence: 99%
“…and how can the outbreak be mitigated with certain intervention approaches [58,7]. Answering those questions requires the use of assumptive parameters as well as actual outbreak data [7,58,26,15]. Our results showed that using information on within-host infection dynamics allows the identification of those key characteristics in the disease transmission.…”
mentioning
confidence: 89%
“…http://dx.doi.org/10.1101/133421 doi: bioRxiv preprint first posted online Nguyen et al The interplays between within-host infection and between hosts transmission led to arising attempts connecting the two levels [14,21,22,12,23,24,25,4], but the approach is still at its infancy [13]. On one hand, most of these models were conceptual and theoretical [13] or rely on assumptive and previously obtained parameter estimates [26,15,27]. We propose that this limitation can be overcome by using explicitly within-host infection model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity in equation (1), and particularly the version in which I(0) = 1, is used extensively in the epidemiological modelling literature [8,9,21,[26][27][28][29][30][31][32][33][34][35]. It is increasingly used in real-time during emerging outbreaks.…”
Section: Introductionmentioning
confidence: 99%